Public-private partnerships in sexual and reproductive healthcare provision: establishing a gender analysis. Issue 2 (4th May 2017) - Gideon, Jasmine; Hunter, Benjamin M.; Murray, Susan F.
ABSTRACT: The past few decades have seen the growing popularity of public-private partnerships (PPPs) across the health sector – a catch all term used to encompass diverse activities involving both public and private sector entities in areas of global and domestic health. In the article we consider the factors that have led to this proliferation of PPPs in the healthcare delivery field and consider the link to the process of 'scientization' of healthcare. With a focus on sexual and reproductive health the article also considers two commonly used mechanisms employed in SRH service delivery that have been used in PPPs – social franchise and health voucher schemes. We then reprise key points from the existing critical literature on gendered health systems and go on to consider their application to such service provision-oriented PPPs, using an exploratory analysis of a case study of the use of maternal health vouchers in India.